EU - do you hear me? : the role of civil society organisations in the democratisation of the European Union - Tykkyläinen, Saila (2009)
The purpose of this thesis is to analyse the role of civil society organisations in enhancing the democracy of the European Union. The question is studied within the framework of discursive democracy, which draws its inspiration from the theory of communicative action by Jürgen Habermas. The research material is consisted of communication policy initiatives of the European Commission and statements of a European network of civil society organisations, the Active citizenship network. I elaborated the question through the concepts of public sphere, horizontal subsidiarity, and a political role of the civil society organisations. Also the contradiction found between citizens' direct participation and the intermediatory role of the civil society organisations (hereafter CSOs), turned out to be a central dimension for the study. The analysis shows that the aspirations of the Commission and the Active citizenship network (hereafter ACN) diverge considerably considering the premises and goals of CSOs' participation within the EU polity. The Commission wants to form partnerships with them, to enhance the quality of its policy-output, and to reach out for its citizens. The ACN, on the other hand, sees organisations as key actors in policy-making, and seeks a strong role for them. However, both parties favor representative democracy. Consequently, neither of them introduce direct participation channels for citizens nor pay due attention to the communicative aspect of democracy. To conclude, I end up suggesting that in order to bring the citizens back in politics without putting their autonomy in danger, and to ensure the political influence of both CSOs and citizens, autonomous public spheres and the guidelines provided by the horizontal subsidiarity should be combined. This way the democratic practices based on unrestricted communication of citizens would cover the whole policy-circle, from the policyformulation to the evaluation of policies.